Developing a congenital hyperinsulinism prioritized research agenda: a patient-driven international collaborative research network - Pasquini, Tai L. S.; Banerjee, Indraneel; Christesen, Henrik Thybo; Conwell, Louise S.; Dastamani, Antonia; De Leon, Diva D.; Flanagan, Sarah E.; Gillis, David; Kalish, Jennifer M.; Lord, Katherine; Mesfin, Mahlet; Schmitt, Jennifer; et al. (Frontiers in Endocrinology, 2025)
IntroductionCongenital Hyperinsulinism (HI) is a rare disease that causes severe and recurrent hypoglycemia due to dysregulated insulin secretion. HI is the most frequent cause of severe, persistent hypoglycemia in newborns and children. Disease management is focused on preventing the neurological consequences associated with hypoglycemic brain injury; however, treatment is complex, often suboptimal, and places a large burden on families and individuals living with HI. Congenital Hyperinsulinism International (CHI) is an international patient organization that received a grant from the Chan Zuckerberg Initiative to establish the CHI Collaborative Research Network (CRN), a collaborative body to accelerate research for HI.Assessment processStakeholder groups relevant to HI, including individuals living with HI, families, researchers, clinicians, nurses, and industry partners, were identified to join the CRN and work together to create a prioritized research agenda (PRA) to systematically rank research priorities. CRN members worked across 7 workstream groups through a structured process to brainstorm gaps and corresponding solutions to formalize the HI PRA.Actionable recommendationsA total of 362 gaps were identified across research, infrastructure, knowledge, and funding. All groups identified the need for an HI Natural History Study; therefore, this item was identified as a priority that would automatically be placed on the finalized list. Other top gaps identified in the PRA addressed preventing brain damage and the need to increase awareness and understanding related to the role of early and effective diagnosis in preventing brain damage.DiscussionThe formation of the CRN and the development of the PRA have already led to new collaborations, which are fundamental to progress. The PRA process allowed individuals to come to a consensus on the critical needs and to chart short- and long-term approaches to fill the gaps. CRN members continue to meet regularly in working groups focused on special projects to fill gaps identified as high priority by the PRA. Through this active and multidimensional alliance, the CRN is re-imagining the future for people living with HI by improving outcomes through more timely and accurate diagnosis, more effective and less burdensome treatments, more easily obtainable expert care, and better tools to manage HI.